Investigation of soluble gas stabilization combined with modified atmosphere packaging on the shelf life of cooked blue mussels (Mytilus edulis) (Research, Society and Development, 2021)
For the use of carbon dioxide in modified packaging (MA) systems, is it necessary a high gas/product ratio to ensure the bacteriostatic effect of fishery food. The use of techniques such as CO2 Soluble Gas Stabilization (SGS), can reduce the size of package necessary to maintain the effectiveness of MA. Thus, the effect of the MA packaging combined with soluble gas stabilization (SGS) as pre-treatment was studied to investigate the shelf life of cooked blue mussels. The samples were subjected at 100% food-grade CO2 (96%) for 2 h (SGS), in large flexible pouch. After SGS treatment, 100 g of mussels were packaged under modified atmosphere and air. Initial CO2 concentration under SGS packages was 70.0 % and remained constant (72.5 %) due the pre-treatment with CO2. Physicochemical properties (pH, water content, firmness and water-holding capacity) were not influenced significantly SGS treatments. The SGS samples had reduced growth of mesophilic and psychrotrophic during storage. The application of SGS resulted in an increased microbiological shelf life (19 days) compared with the packaging with air (5 days) and can contribute to improved quality of cooked mussels.